2017
DOI: 10.1002/bjs.10600
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in mortality after abdominal aortic aneurysm repair in the UK

Abstract: BackgroundThe UK abdominal aortic aneurysm (AAA) screening programmes currently invite only men for screening because the benefit in women is uncertain. Perioperative risk is critical in determining the effectiveness of screening, and contemporary estimates of these risks in women are lacking. The aim of this study was to compare mortality following AAA repair between women and men in the UK.MethodsAnonymized data from the UK National Vascular Registry (NVR) for patients undergoing AAA repair (January 2010 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 37 publications
5
41
0
Order By: Relevance
“…The contemporary real-world data on outcomes following emergency EVAR and open repair of ruptured and intact AAA in this study support existing evidence 4,18,19,24,25 that EVAR is associated with reduced in-hospital mortality. However, it should be noted that women even had higher rates of postoperative in-hospital mortality following EVAR compared with men.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The contemporary real-world data on outcomes following emergency EVAR and open repair of ruptured and intact AAA in this study support existing evidence 4,18,19,24,25 that EVAR is associated with reduced in-hospital mortality. However, it should be noted that women even had higher rates of postoperative in-hospital mortality following EVAR compared with men.…”
Section: Discussionsupporting
confidence: 82%
“…A recent study 18 using the English National Health Service (NHS) administrative data set and UK National Vascular Registry data demonstrated that in-hospital mortality following elective as well as ruptured AAA is worse in women; this confirmed the findings of previous studies 19 -22 that used national databases and registries, and demonstrated higher mortality rates following repair of AAA among women. A recent economic evaluation supported by clinical outcome data from an administrative data set and national registry reported that screening women for AAA is not cost-effective under various scenarios, including starting screening at an older age 23 .…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…Abdominal aortic aneurysm (AAA) is four to six times more common in men than in women, but women have an increased risk of rupture at smaller aneurysm diameter. For intact AAA, women are less often eligible for endovascular aortic repair (EVAR) and have worse outcomes, but such sex differences are debated regarding patients with ruptured AAA (rAAA). Although the incidence of rAAA seems to be declining in general, it is unclear whether this is true for both men and women.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies are based on observational data, and potentially affected by selection bias and confounding factors. Although some researchers adjust for confounders, residual confounding may still be substantial. Several countries have introduced population‐based screening of 65‐year‐old men only.…”
Section: Introductionmentioning
confidence: 99%